A Study on Performance and the Growth of Micro Small & Medium Enterprises (MSMEs) in Tamil Nadu - Manimuthu, G. (International Journal of Psychosocial Rehabilitation, 2020)
Micro Small & Medium Enterprises (MSMEs) plays an important and strategic role in the economic growth and equitable development of a country. Worldwide, the Micro Small & Medium Enterprises (MSMEs) are accepted as prime drivers for employment generation and growth of GDP, besides contributing to the balanced regional development. MSMEs are in a very unique position to become global players attracting partners with technology and funds. These enterprises impart the resilience to resist economic upheavals and maintain an affordable rate of growth since being Indigenous is that the key to sustainability and self sufficiency. In this study analysis of Trends in the Growth of MSMEs in Tamil Nadu by analyzing their Number of Registered units, Investment, Production and employment of MSME in Tamilnadu.